Integrating Exposure and Response Prevention With a Mobile App to Treat Obsessive-Compulsive Disorder: Feasibility, Acceptability, and Preliminary Effects. Issue 2 (March 2021) - Gershkovich, Marina; Middleton, Rachel; Hezel, Dianne M.; Grimaldi, Stephanie; Renna, Megan; Basaraba, Cale; Patel, Sapana; Simpson, H. Blair
Abstract: Many individuals with obsessive-compulsive disorder (OCD) do not receive evidence-based care (specifically exposure and ritual prevention; EX/RP) due to barriers such as a lack of EX/RP-trained clinicians, geographic obstacles, and the cost and time associated with the treatment. Offering an integrated treatment model consisting of brief in-person therapy coupled with a mobile application (app) might be one way to increase access to and reduce the time burden (to clinicians and patients) of EX/RP. This pilot trial evaluated the feasibility, acceptability, and clinical effects of such a treatment program for adults with OCD. Thirty-three participants enrolled in the 8-week open trial. The integrated treatment program consisted of 3 to 5 in-person sessions followed by weekly phone calls supported by a mobile app (nOCD). Participants were evaluated by trained raters and completed self-report measures at baseline, midtreatment, posttreatment and 2-month follow-up; the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) was the primary outcome. This integrated treatment program was feasible and acceptable to participants. Of the 33 study entrants, 14 (42%) responded to treatment (Y-BOCS decrease ≥ 35% with CGI- of 1 or 2), and 8 (24%) achieved minimal symptoms (i.e., Y-BOCS ≤ 12). At 2-month follow-up ( n = 20), 7/20 (35%) met criteria for treatment response, and 3/20 (15.0%) met criteria for treatment remission. Although preliminary, this model warrants further study as an efficacious and resource-efficient way to deliver EX/RP for some patients with OCD. Highlights: Evaluated combining brief exposure and ritual prevention with a mobile app for OCD An 8-week open trial suggests that the program may be acceptable and feasible Some participants showed clinically meaningful reductions in OCD symptoms